Advances in Rheumatology
Advances in Rheumatology is an international, open access journal publishing pre-clinical, translational and clinical studies on all aspects of paediatric and adult rheumatic diseases, including degenerative, inflammatory and autoimmune conditions. The journal is the official publication of the Brazilian Society of Rheumatology and welcomes original research (including systematic reviews and meta-analyses), literature reviews, guidelines and letters arising from published material.